Phenotypic and Genotypic Characteristics and Resistance Profile of Staphylococcus spp. from Bovine Mastitis - Lucio, Érica Chaves; Gouveia, Gisele Veneroni; da Costa, Mateus Matiuzzi; de Oliveira, Mário Baltazar; Mota, Rinaldo Aparecido; Pinheiro Junior, José Wilton (Acta Scientiae Veterinariae, 2020)
Background: Bovine mastitis remains one of the health problems that cause the most damage to milk producers. The negative impact of mastitis is due to reduced milk production, early slaughter of females, reduced commercial value of the affected animals, losses in the genetic potential of the herd, expenses with medicines and veterinary medical assistance. Staphylococcus spp. stands out as the cause of this disease and has been able to remain in the mammary gland, becoming resistant to several antimicrobials. The aims of the present study were to characterize the phenotypes, genotypes and resistance profiles of Staphylococcus spp. isolates from bovine mastitis cases in the state of Pernambuco, Brazil. Materials, Methods & Results: These isolates were classified according to biochemical tests and the presence of the nuc gene. The polymerase chain reaction (PCR) for amplification of the mecA and blaZ genes was used to analyze the genetic potentials of antimicrobial resistance. Isolates were also phenotypically tested for resistance to nine antimicrobials (ampicillin, doxicillin, erythromycin, gentamicin, rifampicin, cephalothin, amoxicillin, nalidixic acid and oxacillin). The genetic potentials for biofilm production were evaluated by the amplifications of the icaD, icaA and bap genes. The phenotypic test of gentian violet was used for biofilm formation analyzes. Ninety-three (93.0%) of the isolates among the Staphylococcus spp. samples were classified as Staphylococcus aureus. The lowest percentage of sensitivity observed was for amoxicillin (28.0%). All of the isolates were sensitive to erythromycin and gentamicin, and 15 (15%) exhibited sensitivity to all of the drugs tested. All of the isolates were negative for the mecA gene, and 36 (36%) were positive for blaZ. In the adhesion microplate tests, 44 (44%) of the isolates were capable of biofilm formation. Of these, seven (15.9%) were strong formers, whereas 16 (36.3%) and 21 (47.8%) were moderate and weak formers, respectively. The icaD gene was confirmed in 89 (89%) of the isolates. The icaA gene was confirmed in 61 (61%) samples, and the bap gene in 52 (52%) samples. One of the samples did not possess icaA, icaD or bap and exhibited moderate biofilm formation according to the microplate adherence test. Sixteen isolates simultaneously exhibited the three genes tested for biofilm production (icaA, icaD and bap) and were negative according to the microplate adherence test. Discussion: The indiscriminate use of antibiotics to treat mastitis is a common practice in the study area, which may have contributed to the high proportion of herds (88.23%; 15/17) with multi-resistant isolates, constituting a selection factor for the dissemination of resistant bacteria among herds. The absence of the mecA gene in the present study may be associated with the development of resistant bacteria through another mechanism, such as the overproduction of beta-lactamases. The results demonstrate that antimicrobial resistance occurs in Staphylococcus spp. that cause bovine mastitis in herds of Pernambuco and that these isolates have the a great capacity for biofilm formation. It is necessary to sensitize the professionals involved in the milk production chain of Brazil regarding the importance of the adequate use of antimicrobials for the treatment and control of mastitis, since studies in the country indicate the dissemination of resistant bacterial strains.